A case of incomplete Miller Fisher syndrome associated with multiple cranial neuritis and sphincter disturbance. Issue 4 (21st June 2018) - Hosokawa, Kyoko; Suzuki, Hidefumi; Ono, Michio; Kojima, Yasuhiro; Kanda, Masutaro; Shibasaki, Hiroshi
Abstract: A 60‐year‐old man, following diarrhea for 2 weeks, acutely developed double vision, unsteady gait, and difficulty in urination, followed by severe dysphagia and bilateral peripheral facial palsy. In view of the preserved anal sphincter and bulbocavernosus reflexes, the sphincter disturbance was ascribed to a brainstem lesion. Serum antibodies against gangliosides including GQ1b were negative. With the clinical diagnosis of incomplete Miller Fisher syndrome combined with multiple cranial neuritis and a possible brainstem lesion, the patient was treated with intravenous immunoglobulin, and most symptoms have improved.